A case report on a rare primary bone tumour: sacral chordoma presenting as sacral swelling with sphincter dysfunction - A. Latheef, Nashwa; James, Emmanuel; Paulose, Leo; Karilly, Praveen; Karuthillam, Premkumar (International Surgery Journal, 2024)
Chordoma is a rare, locally aggressive malignant tumour arising from remnants of the notochord, primarily affecting the axial skeleton, seen twice often in males above 40 years. This case report presents a 50-year-old male with primary sacral chordoma, emphasizing the need for early evaluation, treatment modalities and focusing on the importance of sacral nerve preservation during surgery for better functional outcome. Purpose of the study was to demonstrate the significance of early evaluation and diagnosis, emphasizing the importance of at least unilateral sacral nerve root preservation for optimizing postoperative bowel and bladder function. A 50-year-old male presented with sacral swelling, saddle anaesthesia, lower backache, urinary incontinence, and constipation. Examination revealed a firm, immobile sacral mass with reduced anal sphincter tone. Magnetic resonance imaging (MRI) suggested the presence of a sacral chordoma, leading to the planning of surgical resection. Intraoperatively, frozen section analysis confirmed the diagnosis of chordoma. Intraoperatively, the lesion was found to extend predominantly toward the left side, necessitating careful dissection and preservation of the sacral nerve roots on the right side. Post-operatively, the patient experienced improved bowel and bladder function, along with significant pain relief. The patient showed substantial postoperative improvement, with resolution of urinary and bowel dysfunction. Follow-up imaging revealed no tumour recurrence. Preservation of sacral nerve roots was crucial to the patient’s recovery, improving overall quality of life. This case highlights the need to consider chordoma in the differential diagnosis of sacral masses and emphasizes the importance of sacral nerve root preservation during resection to optimize functional outcomes in patients with this rare tumour.